The Role of Teachers in Implementing an Independent Learning System for Lower Grade Students - Fitria Shinta Dewi (Jurnal Ilmiah Sekolah Dasar, 2022)
There are still many students who find it difficult to ask questions about material that they don't understand, students who get bored easily in the teaching and learning process, and students who don't follow the lesson and play more when learning is in progress are the main reasons for the importance of the teacher's role in educating, directing and providing good learning media so that students are interested in participating in learning. This study aims to analyze the role of teachers in implementing an independent learning system for low-grade students. This study uses a qualitative approach with a descriptive method. The research subjects were four people, one principal, and 3 class teachers. At the same time, the test subjects were 75 students (1 class each at 3 levels). Then, the data collection techniques used were interviews, observation, and documentation. Meanwhile, data analysis is done by collecting information through interviews, data reduction, and data presentation. The results showed that the teacher's role in implementing independent learning in lower grade students had been carried out to the maximum. Teachers have used various learning methods to make students interested, not bored, and enthusiastic in the teaching and learning, including giving gifts, praise, yelling, and punishment/reprimand if students behave badly in learning.